KUALITAS PELET TIGA JENIS KAYU: BANGKIRAI (Shorea laevis Rdl), SUNGKAI (Peronema canescens Jack) DAN MERANTI MERAH (Shorea leprosula Mig): Lies Indrayanti 1 , Alpian 1 , * Wahyu Supriyati 1 , Renhart Jemi 1 ,Theresia Anggreini Sirait 1 , Rosdiana 1 - editor (Agrienvi: Jurnal Ilmu Pertanian, 2020)
One of the ways to support zero waste policies in the timber industry was used the industry wastemaximally. Sawdust is probable materials to produce wood pellet. This research aims to identify the quality ofwood pellet of Bangkirai, Sungkai, and red Meranti. Tapioca flour will be used as an adhesive material. Secondly,to identify the feasibility of those three types of timber as wood pellet, that can be used either as domesticconsumption or export. Research used complete-random design with timber as the factor. The result shows thatwood pellet yielded from Sungkai has better quality than wood pellet produced from the other two timber types.The difference in type of wood is only the density value shows very significant effect. Overall, the research resulthas qualified for SNI standard (8201-2014) and France standard (ITEBE). However, only several parts ofparameters from three types of timber that conform with Sweden standard (SS187120). Those three types oftimber are feasibly usable and prospective to be developed as wood pellet material. But, intensive handling of thepellet's water content and testing of mechanical properties and durability were needed.Keywords: wood pellet, sawdust, standard quality, prospective.